2017
DOI: 10.1097/lgt.0000000000000267
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Vulvar and Peripheral Sensitivity Among Women With Vulvodynia: A Case–Control Study

Abstract: Objective To assess differences in vulvar and peripheral sensitivity between women with and without vulvodynia. Methods Women with vulvodynia (N=41) and age-matched controls (N=43) seen in the outpatient setting were evaluated via surveys, clinical examination, and multimodal sensory testing (pressure, heat, cold, vibration, and electrical stimulation). The relationship between sensitivity to various sensory modalities and case/control status, as well as by vulvodynia subgroups, were assessed using logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
(46 reference statements)
1
10
0
Order By: Relevance
“…Tenderness of the bladder and pelvic floor, as well as the diagnosis of PBS, have been associated with deep dyspareunia in previous literature as well [92,93]. It should also be emphasized that IC/PBS is associated with vulvodynia [94], and thus is also related to superficial dyspareunia.…”
Section: Interstitial Cystitis/painful Bladder Syndromementioning
confidence: 85%
“…Tenderness of the bladder and pelvic floor, as well as the diagnosis of PBS, have been associated with deep dyspareunia in previous literature as well [92,93]. It should also be emphasized that IC/PBS is associated with vulvodynia [94], and thus is also related to superficial dyspareunia.…”
Section: Interstitial Cystitis/painful Bladder Syndromementioning
confidence: 85%
“…Reed, et al, assessed differences in vulvar and peripheral sensitivity and similarly found women with vulvodynia were more sensitive to pressure and electrical stimuli than were control women at the vulva and at the thumb. 15 Foster, et al, compared the response to intradermal capsaicin at the forearm and foot of women with vestibulodynia to controls, and found that patients with vestibulodynia demonstrated altered pain processing extending to regions far beyond the vulva. 4 Hampson, et al, found augmented brain activation on fMRI studies in women with vulvodynia…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found an increased density of nerve fibers in affected vulvar tissue (59) and a lower threshold for pain in extremities which could indicate peripheral and central sensitization (60). Furthermore, other chronic pain conditions such as fibromyalgia and irritable bowel syndrome are more common in women with LPV (51,61).…”
Section: Vulvodyniamentioning
confidence: 99%
“…• An altered pain-processing in the brain (76), higher gray matter density in painmodulatory and stress-related areas (77) as well as general allodynia to mechanical pressure as measured in the thumb (60) has been observed in women with LPV which could indicate central sensitization (78) .…”
Section: Vulvodyniamentioning
confidence: 99%